Morphometric evaluation by ultrasonographic exam of the portal veinm vaudal vein and abdominal aorta in healthy dogs of diferent body weights - Sartor, Raquel [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Takahira, Regina Kiomi [UNESP] (Universidade Federal do Paraná, 2010)
The diameters and areas of portal vein, caudal vena cava and abdominal aorta are useful measurements in dogs. These values can be easily measured by ultrasonographic exam, and variations of normality can be an important indicator of hepatic or extra-hepatic alterations. This study aimed to measure the diameter and areas of portal vein, caudal vena cava and abdominal aorta inhealthy dogs, with normal corporal score, divided in groups according to the body weight, and assess whether the data are influenced by animal weight. Thirty dogs were examined and divided into three groups (Group A: ≤ 10 kg Group B: from 10.1 to 20.0 kg; Group C: ≥ 20.1 kg). To measure thediameters and areas of portal vein, caudal vena cava and abdominal aorta, the animal was kept in left lateral decubitus position and the transducer was placed on the right lateral abdominal wall, at approximately the 10th or 11th intercostal space, in the porta hepatis region. The diameters and areas of the portal vein, caudal vena cava and abdominal aorta were significantly lower for dogs in Group A with respect to other groups and the dogs from Groups B and C had similar results with each other. The diameters and areas of the portal vein, caudal vena cava and abdominal aorta may vary with the animal size, and reference values must be specific for small, medium and large dogs. Key words: abdominal vessels; area; diameter; measurement; ultrasonographic exam

Os diâmetros e áreas da veia porta, veia cava caudal e aorta abdominal são mensurações importantes a serem realizadas durante o exame ultrassonográfico abdominal no cão. Tais valores podem ser facilmente mensurados, e a detecção de valores fora do padrão de normalidade pode ser considerada um importante indicador de alterações hepáticas, ou extra-hepáticas. O objetivo deste estudo é mensurar os diâmetros e as áreas da veia porta, veia cava caudal e da aorta abdominal em cães hígidos, divididos em grupos, de acordo com o peso corporal, para determinar valores de normalidade e avaliar a influência do peso corpóreo nestes valores. Foram examinados 30 cães divididos em três grupos (Grupo A: ≤ 10 kg; Grupo B: de 10,1 a 20,0 kg; Group C: ≥ 20,1 kg). Para medir os diâmetros e áreas da veia porta, veia cava caudal, e aorta abdominal, os animais foram mantidos em decúbito lateral esquerdo e o transdutor foi posicionado na parede abdominal lateral direita, aproximadamente no 10º ou 11º espaço intercostal, na região porta hepatis. Os diâmetros e áreas da veia porta, veia cava caudal e aorta abdominal, foram menores nos cães do Grupo A com relação aos outros Grupos (P<0,01), enquanto os cães dos Grupos B e C tiveram resultados semelhantes entre eles (P> 0,05). Concluiu-se que tanto o diâmetro quanto a área da veia porta, veia cava caudal e aorta abdominal variam com o tamanho do animal, e os valores de referência devem ser específicos de acordo com o porte do cão.
Avaliação morfométrica, realizada pelo exame ultrassonográfico, da veia porta, veia cava caudal e aorta abdominal em cães saudáveis de diferentes pesos corpóreos
Keywords: Abdominal vessels; Area; Diameter; Measurement; Ultrasonographic exam; Área; Diâmetro; Mensuração; Ultrassonografia; Vasos abdominais